Product Value as a Determinant of Opec's Official Crude Oil Prices: Additional Evidence - Lowinger, Thomas C.; Ram, Rati (The Review of Economics and Statistics, 1984)
,_ The Rate of Imitation of a Capital-Embodied Process Innovation, Economica 44 (Feb. 1977), 63-69. Sahal, Devendra, Patterns of Technological Innovation (Reading, MA: Addison-Wesley, 1981). Saxonhouse, Gary R., Estimated Parameters as Dependent Variables, American Economic Review 66 (Mar. 1976), 178-183. Theil, Henri, On the Estimation of Relationships Involving Qualitative Variables, American Journal of Sociology 76 (July 1970), 103-154. , Principles of Econometrics (New York: Wiley & Sons, 1971). Walker, David, An Analysis of Financial and Structural Characteristics of Banks with Retail EFT Machines, Working Paper # 79-1, FDIC, 1979.